Research priorities for randomised controlled trials in chronic migraine preventive medication: A stakeholder consensus workshop [version 2; peer review: 1 approved, 2 approved with reservations] - Martin Underwood; Andrew Cooklin; Sophie Rees; Manjit Matharu; Callum Duncan; Hema Mistry; Seyran Naghdi (NIHR Open Research)
Background Chronic migraine is a disabling condition that can substantially impact on quality of life. People with chronic migraine have headaches on at least 15 days of every month. Preventative medications aiming to reduce number of days with migraine are available, but high-quality randomised evidence is lacking for many drugs, and it is unclear which medications should be prioritised for research. There is also no existing evidence about patient and clinicians’ priorities for research. Methods We undertook a consensus workshop with patient and healthcare professional stakeholders, using nominal group technique, to understand these stakeholders’ priorities for future randomised controlled trials. We reached a consensus on a set of research recommendations for the field. Results Eight people with chronic migraine and eleven healthcare professionals took part in an online workshop. Comparisons of calcitonin gene-related peptide monoclonal antibodies (CGRP MAbs) and OnabotulinumtoxinA (BTA) were a top priority for our group. Candesartan and Flunarizine were the top drugs the group wanted to compare against placebo. Conclusions These research recommendations should guide researchers in the field, and funders when prioritising commissioned research and assessing funding applications. Particular areas to explore further are Candesartan or Flunarizine versus placebo, and comparing and combining CGRP MAbs with other medications.